Characteristic of Concrete made of Ternary Cementitious System - Siregar, Atur P. N. (Jurusan Teknik Sipil Universitas Tadulako, 2015)
Utilizing industrial waste materials containing pozolanic compounds has been widely investigated for cementÂ replacement. Fly ash and microsilica are materials having significant pozolanic compounds and can be used to create ternary cementitious system. Slump of fresh concrete, porosity and compressive strength of hardened concrete were parametric study investigated in this study of ternary cementitious system.Â Three types of concrete mixtures, i.e. concrete mixture using original Portland cement (OPC) as normal concrete, OPC-fly ash-microslica without superplasticiser, and OPC-fly ash-microslica with additional superplasticiser have been investigated. Fresh concrete using fly ash and microsilica demonstrated having higher slump and lower porosity than normal concrete. Compressive strength of concrete using fly ash and microsilica were higher than normal concrete. Utilizing fly ash and microsilica as ternary cementitious system was found to have significant effect on compressive strength and porosity of hardened concrete.